Acute and chronic infection of H. pylori caused the difference in apoptosis of gastric epithelial cells. (January 2021) - Liu, Jia-Fei; Guo, Dong; Kang, En-Ming; Wang, Yu-Shan; Gao, Xiao-Zhong; Cong, Hai-Yan; Liu, Peng; Zhang, Nai-Qian; Wang, Ming-Yi
Abstract: Helicobacter pylori ( H. pylori ) is one of the most important pathogenic bacteria associated with various gastrointestinal diseases. At present, its apoptotic or antiapoptotic mechanism on gastric epithelial cells remains unknown and needs further illustrated. In this study, acute infection model ( H. pylori and GES-1 cells were co-cultured for 24 h at a multiplicity of infection MOI of 100:1) and chronic infection model (GES-1 cells were infected repeatedly every 24 h at a multiplicity of infection MOI of 100:1 for approximately 8 weeks) were established, respectively. the chronic H. pylori infected GES-1 cells underwent a typically morphological change and Western Blot results showed that there was slight decrease in expression of E-cadherin, and obvious increase in expression of Vimentin. Apoptosis of these two models were analyzed by flow cytometry compared with the control cells, meanwhile, apoptosis associated markers (Bcl-xL, Bcl-2, Bax, etc) were detected by Western blot, additional in clinical H. pylori -positive gastric cancer tissues. Results showed that compared with the control cells, acute infection of H. pylori significantly accelerated the apoptosis of GES-1, increased the expression of Bax and Cleaved caspase-3, down-regulated expression of Bcl-xL and Bcl-2. Moreover, an opposite result was found in chronic infection of model and clinical gastric cancer tissues, and enhanced expression of NF–κB p65. Taken together, these findings suggest that H. pylori infection plays differential effects on apoptosis of gastric epithelial cells. Highlights: Acute infection with H. pylori promotes gastric epithelial cell apoptosis. Chronic infection with H. pylori induced the epithelial-to-mesenchymal transition and enhanced the apoptosis tolerance. The changes of apoptosis of GES-1 cells induced by H. pylori infection were mainly caused by different changes of the mitochondrial apoptosis pathway and NF-κB signaling pathway.